Around the world in 80 days - Verne, Jules; Dickmann, Daniele (Usborne Publishing London, 2017)
"Shocking his stodgy colleagues at the exclusive Reform Club, enigmatic Englishman Phileas Fogg wagers his fortune, undertaking an extraordinary and daring enterprise: to circumnavigate the globe in eighty days. With his French valet Passepartout in tow, Verne's hero traverses the far reaches of the earth, all the while tracked by the intrepid Detective Fix, a bounty hunter certain he is on the trail of a notorious bank robber." --Publisher description